Covid-19 and Implementation of Airport Health and Safety Procedures: The Safety Culture Perception - Nugraha, Wildan; Amalia, Direstu (Syntax Literate, 2021)
The Covid-19 pandemic that is currently happening has become a scourge for the community and has had a quite wide impact on almost all industrial sectors, especially in the aviation industry. Government directions that require individuals to carry out social and physical distancing have made noteworthy changes to the flight forms and methods. The aim of this research is to assess the effect of implementing policies or regulations issued by the government regarding the handling of Covid-19 on aviation safety, especially in the airport operations sector. The approach of this research is descriptive qualitative, while data collection uses interview techniques and distributing questionnaires to airport personnel and airport management. This study resulted in findings that the aspect of aviation safety, especially for users of air transportation services, remains a top priority for airport operators even though during the Covid-19 pandemic, this is evidenced by the application of Biosafety Management and Biosecurity Management in the implementation of flight operations at airports. however, it is necessary to establish good collaboration and coordination with operators between modes of transportation other than aircraft in the airport area to prioritize the safety of users of transportation services by implementing health protocols.